A Streetcar Named Desire: Chelsea Walker on Directing - Williams, Tennessee (Digital Theatre+, 2018)
Chelsea Walker provides an in-depth analysis of Tennessee Williams' 'A Streetcar Named Desire' and reveals her intentions for staging the play at the Nuffield Theatre, Southampton in 2018.